2017
DOI: 10.18632/oncotarget.15202
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter matched case-control analysis on seven polymorphisms from HMGB1 and RAGE genes in predicting hepatocellular carcinoma risk

Abstract: Based on 540 hepatocellular carcinoma patients and 540 age- and gender-matched controls, we tested the hypothesis that high mobility group protein box1 (HMGB1) and the receptor for advanced glycation end products (RAGE) genes are two potential candidate susceptibility genes for hepatocellular carcinoma in a multicenter hospital-based case-control analysis. The genotypes of seven widely-studied polymorphisms were determined, and their distributions respected the Hardy-Weinberg equilibrium. The mutant alleles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Sensitivity analysis was performed by removing one study at a time to assess the stability of these results. After the removal of Wang et al study 25 , the resulting heterogeneity across studies decreased from moderate heterogeneity ( χ2 = 17.31; df = 8; p =0.03; I 2 = 54%) to low ( χ2 = 7.14; df = 7; p =0.41; I 2 = 2%) in the dominant model (TT vs. CC+TC). However, after eliminating the Wang et al study 25 , the pooled ORs were not distinctly changed, with stable results.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Sensitivity analysis was performed by removing one study at a time to assess the stability of these results. After the removal of Wang et al study 25 , the resulting heterogeneity across studies decreased from moderate heterogeneity ( χ2 = 17.31; df = 8; p =0.03; I 2 = 54%) to low ( χ2 = 7.14; df = 7; p =0.41; I 2 = 2%) in the dominant model (TT vs. CC+TC). However, after eliminating the Wang et al study 25 , the pooled ORs were not distinctly changed, with stable results.…”
Section: Resultsmentioning
confidence: 96%
“…After the removal of Wang et al study 25 , the resulting heterogeneity across studies decreased from moderate heterogeneity ( χ2 = 17.31; df = 8; p =0.03; I 2 = 54%) to low ( χ2 = 7.14; df = 7; p =0.41; I 2 = 2%) in the dominant model (TT vs. CC+TC). However, after eliminating the Wang et al study 25 , the pooled ORs were not distinctly changed, with stable results. Funnel plots were drawn to determine the risk of bias, and they were symmetric (Figure 5 ), indicating the absence of publication bias.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, HMGB1 was suggested as a novel target for potential therapeutics since highly expressed HMGB1 was found to be associated with the epithelial-to-mesenchymal transition (EMT) and the overexpression of MMP-1, MMP-3, and MMP-10 via the RAGE/NF-κB signaling pathways, facilitating prostate cancer metastasis [ 1 , 16 , 17 , 18 , 19 , 20 ]. Furthermore, polymorphisms of HMGB1 have been associated with many cancers, including oral squamous cell carcinoma (OSCC) [ 21 , 22 ], lung cancer [ 23 , 24 , 25 , 26 ], breast cancer [ 27 , 28 , 29 ], gastric cancer [ 30 ], hepatocellular carcinoma (HCC) [ 31 , 32 ], and colorectal cancer (CRC) [ 33 ], and it was suggested that the SNPs of HMGB1 may provide a potential biomarker for predicting cancer risk, tumor development, or chemotherapy responses [ 21 , 25 , 27 , 31 ]. However, the impact of HMGB1 polymorphisms on prostate cancer susceptibility and clinicopathologic characteristics has remained uninvestigated.…”
Section: Introductionmentioning
confidence: 99%